Effect of Timing of Initial Cataract Surgery, Compliance to Amblyopia Therapy on Outcomes of Secondary Intraocular Lens Implantation in Chinese Children: A Retrospective Case Series. (22nd March 2018) - Li, Liuyang; Wang, Yan; Xue, Caihong
Abstract : Purpose . As a secondary analysis, we reassess the association of initial congenital cataract surgery times, compliance to amblyopia therapy, and visual outcomes for a long-term follow-up in a secondary IOL implantation. Methods . Retrospective review of records of all infants with congenital cataracts who underwent secondary IOL implantation in the Eye and ENT Hospital of Fudan University from January 1, 2001, to December 31, 2007, and the minimum follow-up period was 5 years. Multiple regression analysis was used and the possible confounding factors were also analyzed to assess the effect on visual outcome. Results . A total of 110 patients (male: 59.1%) were included. The median (min–max) age at cataract extraction and IOL implantation was 7.5 (3.0–15.0) and 35.0 (22.0–184.0) months, respectively, and the average follow-up period was 99.3 ± 23.6 months. The median (min–max) BCVA at final follow-up was 0.20 (0.01–1.00). Compliance to amblyopia therapy was none, poor, and good in 21.8%, 24.5%, and 53.6%, respectively. Postoperative BCVA [logMAR, median (min–max) 0.70 (0.00–2.00)] linearly decreased with increasing cataract extraction time (per month) (β = 0.04, 95% CI: 0.03–0.06, p < 0.0001 ) in multivariable models with laterality and compliance to amblyopia therapy adjusted. Good compliance to amblyopia therapy was associated with better BCVA (logMAR) at last follow-up (β = − 0.40, 95% CI = −0.53 to −0.27, p < 0.0001 ) with laterality, opacity type, and extraction time adjusted. Conclusions . For Chinese infants with congenital cataract, an earlier primary congenital cataract surgery at an age of 3 to 15 months is associated with a better visual outcome. Good compliance to amblyopia therapy was also significant to visual outcome.